Alkyl bicarbamates supramolecular organogelators with effective selective gelation and high oil recovery from oil/water mixtures. (January 2017) - Wang, Yongzhen; Wu, Songquan; Yan, Xingru; Ma, Tao; Shao, Lu; Liu, Yuyan; Guo, Zhanhu
Abstract: A series of alkyl bicarbamates supramolecular organogelators were synthesized with different structures and lengths of alkyl chains. The driving forces for the self-assembly of small molecules, including the intermolecular H bonding, π-π stacking and van der Waals interactions, played an important role in the formation of different 3D network structures, i.e., fibers, ribbons, sheets, and prisms. And a probable formation process of the gel networks was proposed. Furthermore, the phase-selective gelling performances were investigated for oil removal from aqueous solution. Interestingly, the gelling properties were found to be affected by the length and structure of alkyl chains, while some gelators with intermediate alkyl chain lengths could effectively gel all the tested oils from water surface within 15 min, such as Russian crude oil, diesel, gasoline, soybean oil, peanut oil, olive oil, cyclohexane, hexane and ethyl acetate. Advantageously, fast gelation, high rate of oil removal (>95%) and excellent oil retention rate (close to 100%) were realized in the recovery of oil spills from water surface. This kind of supramolecular gelators demonstrates good potential applications in the delivery or removal of organic pollution from oil/water mixtures. Graphical abstract: Image 1 Highlights: A series of alkyl bicarbamates supramolecular organogelators were synthesized. The driving force for small molecules self-assembly was characterized and analyzed. The oil gelator can self-assemble in oils to form different 3D networks. Some gelators can phase-selectively gel and recover oil spills from water surface. The removal of oils is thorough with high oil removal rate and oil retention rate.